2022
DOI: 10.3390/vetsci9070352
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Essential Fatty Acids, Immunoglobulins (IgA, IgG, and IgM), and Enteric Methane Emission in Primiparous Sows Fed Hemp Seed Oil and Their Offspring Response

Abstract: This study shows the effects of dietary hemp seed oil on the milk composition, blood immunoglobulins (Ig), and enteric methane (E-CH4) production of primiparous sows, and their offspring’s response at three time points. A bifactorial experiment was conducted for 21 days (d) on 18 primiparous sows (195 ± 3 days old). The sows were fed two diets: (i) a control diet (SO) based on soybean oil (1.6%), with an 18.82 n-6:n-3 polyunsaturated fatty acids (PUFA) ratio; (ii) an experimental diet (HO) based on hemp seed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…However, the level of colostrum IgM, IgG, and cord blood hemoglobin (Hb) was negatively correlated with the risk of diarrhea in suckling piglets. This is in agreement with the results of a previous study, which found a correlation between higher IgM and IgG group concentrations in sow colostrum and decreased incidence of diarrheal disease in newborn piglets [62]. The development of Hb in cord blood would undoubtedly strengthen piglets' inbuilt immunity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the level of colostrum IgM, IgG, and cord blood hemoglobin (Hb) was negatively correlated with the risk of diarrhea in suckling piglets. This is in agreement with the results of a previous study, which found a correlation between higher IgM and IgG group concentrations in sow colostrum and decreased incidence of diarrheal disease in newborn piglets [62]. The development of Hb in cord blood would undoubtedly strengthen piglets' inbuilt immunity.…”
Section: Discussionsupporting
confidence: 92%
“…The development of Hb in cord blood would undoubtedly strengthen piglets' inbuilt immunity. Immune globulins, primarily IgG and IgM, are thought to be the main components of colostrum protein, and they shield piglets from possible harm caused by pathogenic bacteria [62].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the hypothesis that adding fat-rich ingredients to the diet can reduce the amount of CH 4 produced, we can assume that the SP could mitigate the main GHG. However, there is no evidence in the literature that nutritional strategies are more effective in decreasing the enteric CH 4 level [ 11 ]. On the other hand, it was specified that PUFA inhibits the population of rumen protozoa that produce H 2 .…”
Section: Potential Applications Of Silkworm Pupaementioning
confidence: 99%
“…Most of the investigated vegetable oils have higher PUFA content, notably higher n-6 PUFA concentration; however, some have a higher composition in beneficial n-3 PUFA, such as linseed, hempseed, camelina, pumpkin and sesame oil etc. [ 6 , 8 , 9 , 10 , 11 , 12 ]. The primary issues are related to the low worldwide production and ineffective technologies for processing edible oil from plants [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the immune system is immature, newborn piglets cannot cope with the invasion of pathogens. Immunoglobulin G (IgG), IgM and IgA are crucial for protecting the health of offspring [ 8 ]. The abundant immunoglobulins in colostrum and fatty acids in milk are key for newborn and lactating piglets to keep good health and growth, which are strongly affected by the maternal nutritional status.…”
Section: Introductionmentioning
confidence: 99%